Região de instabilidade em bilhares - Carlos Alberto Salazar Mercado (2019)
This research has as main objective to study a primary instability region o a billiard application to establish conditions to get a Mather’s theorem in a certain topology on ovals billiards and the destruction of nonconvex resonant caustics in a elliptical billiard by the curvature flow.